Needs Analysis for Developing HOTS Sharf Awwal Questions Using a Web-Based LMS - Muhammad Kamal bin Abdul Hakim; Shafruddin Tajuddin; Khambali (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
The direction of learning targets in the modern era is not only at the level of understanding but also at the level of implementing, analyzing, producing, and evaluating, even to the ability to utilize technology such as websites. Sharf lessons are complex lessons. Very few quality questions are found, and educators still use the Lower Order Thinking Skill (LOTS) level, which sometimes causes them to forget that the target of mastering Sharf science is actually to master Arabic. This study aims to produce questions for the evaluation of Sharf Awwal High Order Thinking Skill (HOTS) learning through the Learning Management System (LMS) website. This study is still in the initial research stage using descriptive qualitative methods. The data collection process uses documentation, interviews, and questionnaires. The results show that developing Sharf Awwal HOTS questions using the website must be based on related materials. In addition, the questions that are compiled must lead to practice in producing descriptive and narrative texts, analyzing texts from sources such as the text of the Qur'an, Alhadith, Arabic news, poetry, to the production of dialogue or communicative texts.